Gut microbiota-gonadal axis: the impact of gut microbiota on reproductive functions - Ashonibare, Victory J.; Akorede, Bolaji A.; Ashonibare, Precious J.; Akhigbe, Tunmise M.; Akhigbe, Roland Eghoghosoa (Frontiers in Immunology, 2024)
The influence of gut microbiota on physiological processes is rapidly gaining attention globally.Despite being under-studied, there are available data demonstrating a gut microbiota-gonadal cross-talk, and the importance of this axis in reproduction. This study reviews the impacts of gut microbiota on reproduction. In addition, the possible mechanisms by which gut microbiota modulates male and female reproduction are presented. Databases, including Embase, Google scholar, Pubmed/Medline, Scopus, and Web of Science, were explored using relevant key words.Findings showed that gut microbiota promotes gonadal functions by modulating the circulating levels of steroid sex hormones, insulin sensitivity, immune system, and gonadal microbiota. Gut microbiota also alter ROS generation and the activation of cytokine accumulation. In conclusion, available data demonstrate the existence of a gut microbiota-gonadal axis, and role of this axis on gonadal functions. However, majority of the data were compelling evidences from animal studies with a great dearth of human data. Therefore, human studies validating the reports of experimental studies using animal models are important.